Pressure Correction in the Calibration of Heat Dissipation Sensors - Thomle, J.N. (2020)
Heat dissipation sensors (HDSs) infer soil matric potential based on the measured rate of temperature rise from a heat source. The process for calibrating these sensors may use a pressure plate apparatus (PPA) to remove water to a certain calibration point that is controlled by pressure. Conventionally, the pressure within the PPA is released before the temperature change calibration points are measured (ΔT0). This conventional HDS calibration approach can take several weeks. We propose that the equilibrated temperature change at pressure (ΔTp) can be corrected empirically to the value at zero pressure. Based on measurements of 14 HDSs between 0.02 and 0.1 MPa, ΔTp was on average 6.2% larger than ΔT0. After pressure correction, using an empirical equation, the difference between the corrected ΔTp and ΔT0 was only 0.28%. These results demonstrate that this empirical approach provides sufficient accuracy to achieve HDS calibration without performing a PPA pressure release.